KAJIAN KANDUNGAN GLUKOSA DARAH DAN PRODUKSI SUSU SAPI PERAH DENGAN RANSUM BERBEDA KUALITAS - Utomo B; Sardjana Sardjana; Sudjatmogo Sudjatmogo; A.S. A.S. Pambudi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
The study was conducted with involving members of dairy cattle farming group in Samirono Village, Getasan Subdistrict Semarang Regency. The study was aimed to find out the effect of feeding with various diets for the blood glucose concentration and the milk production of Friesian Holstein dairy cattle. Ox livestock were 15, relocated in 3 different treatments, i.e. TO= Feeding with 12% PK and 65 TDN; Tl= 14% PK and 70 % TDN; and T2 = 16 % PK with 75 % TON. The feeding used bulrush and the concentration comparison was 55 % and 45 %. Beverage was given in ad libitum. Experiment setting used integrated random design with F assessment and Duncan's doubled distance test. Noticed variables were dry fed consumption (BK), blood glucose concentration, milk lactose, milk liquid, and milk production. The result showed that the average consumption of BK TO (8.540 kg/day) was significantly lower (P<0.05) than T2 (10.216 kg/day).The averageblood glucose concentrationsTO (57.796 mg/di), Tl (9.782 mg/di) and T2 (62.722 mg/di) were not different significantly (P>0.05). The average lactose concentration TO (328.904 gram/day), was in fact lower (P<0.05) than TI (462.702 gr/day) and T2 (478.128 gram/day). The average of milk concentration TO (7.096 kg/head/day) was evidently lower (P<0.05) than TI (11.858 kg/head/day). The average of milk production TO (7.919 It/head/day) was evidently lower (P<0.05) from TI (11.277 lt/ head/day) and T2 (13.117 It/head/day). Based on the study, it can be concluded that the in• creasing quality of feeding can raise blood glucose concentration, milk lactose, milk liquid, and milk production.